SYSTEMATIC LITERATURE REVIEW: MODEL PROBLEM BASED LEARNING TERHADAP BERPIKIR KRITIS DALAM PEMBELAJARAN IPS SD - Mulyati, Sri; Ansori, Yoyo Zakaria; Kurino, Yeni Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking, as a core competence of 21st-century learning, must be fostered from the primary school level, particularly through Social Studies instruction that emphasizes social issue analysis and rational decision-making. Empirical evidence indicates that limited critical thinking skills among elementary students are often associated with teacher-centered instructional practices. This study aims to evaluate the effectiveness of the Problem Based Learning (PBL) model in enhancing students’ critical thinking skills in Social Studies through a recent literature review. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Articles published between 2020 and 2025 were retrieved from Google Scholar and Publish or Perish. Based on predefined inclusion and exclusion criteria, ten relevant studies were selected and analyzed thematically. The findings consistently demonstrate that PBL implementation has a positive impact on students’ critical thinking skills, particularly in the areas of analysis, evaluation, inference, and argument construction. However, higher-order components such as drawing conclusions and argumentative synthesis require more structured and sustained application of PBL syntax. The effectiveness of PBL is influenced by internal factors, including students’ learning motivation and active participation, as well as external factors such as the quality of contextual problem design and teachers’ classroom management. Overall, the review confirms that PBL is a relevant and effective instructional model for primary Social Studies education, promoting participatory, contextual, and reflective learning. This study contributes a comprehensive mapping of PBL effectiveness and offers recommendations for strengthening higher-order thinking skills in elementary classrooms.